Does the frequency of HIV and STI testing among men who have sex with men in primary care adhere with Australian guidelines?. Issue 5 (10th May 2010) - Guy, R; Goller, J L; Spelman, T; El-Hayek, C; Gold, J; Lim, M; Leslie, D; Tee, B K; Roth, N; Anderson, J; Fairley, C K; Kaldor, J; et al.
Abstract : Objectives: Australian guidelines recommend annual testing for HIV and sexually transmitted infections (STIs) for all men who have sex with men (MSM) and 3–6 monthly testing for those at higher risk as defined by behavioural criteria. We assessed HIV/STI re-testing rates among MSM attending primary care clinics. Methods: We conducted a retrospective follow-up of HIV negative MSM tested for HIV or STIs (chlamydia or syphilis) at four primary care clinics in the 9-month period: April to December 2006. Re-testing rates for these infections were calculated over 18 months. Logistic regression was undertaken to identify predictors of guideline adherence. Results: Of the MSM requiring annual HIV testing according to the guidelines, the re-testing rates at 1 y were 35% (762/2163). Among the higher risk MSM, 6-monthly HIV re-testing rates were 15% (283/1862). Within the subgroup who reported 11 or more male sexual partners within the past 6 months, HIV re-testing rates within 6 months were 19%. Independent predictors of HIV re-testing within 6 months in higher-risk MSM were reporting 11 or more male sexual partners in the last 6 months (AOR 3.1, 95% CI 1.8 to 4.8); being born overseas (AOR 2.0, 95% CI 1.2 to 3.4); and previous HIV testing more than 12 months earlier (AOR 3.3, 95% CI 1.9 to 5.5). Conclusion: There is poor adherence to national guidelines that recommend regular re-testing of MSM for STIs, particularly among those at higher risk who require more frequent testing. Clinical strategies are urgently needed to encourage more frequent HIV/STI testing among MSM, especially in the higher risk subgroup.